2019
DOI: 10.3390/nu11112820
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Disturbances and the Role of Proper Nutrition in CKD Patients

Abstract: Chronic kidney disease (CKD) is a widespread disease with increasing prevalence in the modern society. Lipid disturbances are common in this group of patients. In most patients with CKD atherogenic dyslipidemia is observed. Dyslipidemia in patients with renal diseases increases the risk of cardiovascular diseases and it accelerates the progression of chronic kidney disease to its end stage. The amelioration of dyslipidemia and the lowering of oxidative stress, inflammatory processes, insulin sensitivity and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 170 publications
(296 reference statements)
0
12
0
Order By: Relevance
“…Cholesterol is essential to cell viability and functions. Cholesterol not only constitutes cell membranes but also serves as a precursor for the biosynthesis of steroid hormones, oxysterols, and bile acids, all of which play critical roles in health and disease ( Sozen and Ozer, 2017 , Benito-Vicente et al., 2018 , Gluba-Brzozka et al., 2019 ). The liver is the main site for cholesterol metabolism and thus serves as a control center for the maintenance of cholesterol homeostasis in the body.…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol is essential to cell viability and functions. Cholesterol not only constitutes cell membranes but also serves as a precursor for the biosynthesis of steroid hormones, oxysterols, and bile acids, all of which play critical roles in health and disease ( Sozen and Ozer, 2017 , Benito-Vicente et al., 2018 , Gluba-Brzozka et al., 2019 ). The liver is the main site for cholesterol metabolism and thus serves as a control center for the maintenance of cholesterol homeostasis in the body.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a large cohort study of 38,377 patients with an eGFR 15–59 ml/min/1.73 m 2 reported that a serum HDL cholesterol level > 60 mg/dl was associated with higher risks of all-cause and cardiovascular mortality in male CKD patients 44 . Although low HDL cholesterol is a typical feature of lipid disturbance in CKD, many reports have demonstrated a decrease in HDL antioxidants and anti-inflammatory activity in patients with CKD at any stage 45 47 . Furthermore, many studies have demonstrated that HDL cholesterol can change from an anti-inflammatory to a pro-inflammatory molecule in patients with advanced CKD 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that cholesterol modulates the bilayer structure parameters of biological membranes, such as thickness, compressibility, water penetration. However, high cholesterol and triglyceride plasma levels have been demonstrated to be important risk factors for the progression of kidney disease and high total cholesterol or reduced HDL (high-density lipoprotein) cholesterol can decrease glomerular filtration rate [ 8 ].…”
Section: Introductionmentioning
confidence: 99%